2015
DOI: 10.1515/amm-2015-0339
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure And Functional Properties Of Prosthetic Cobalt Alloys CoCrW

Abstract: The material subject to investigation was two commercial alloys of cobalt CoCrW (No. 27 and 28) used in prosthodontics. The scope of research included performing an analysis of microstructure and functional properties (microhardness, wear resistance and corrosion resistance), as well as dilatometric tests. The examined alloys were characterized by diverse properties, which was considerably influenced by the morphology of precipitates in these materials. Alloy No. 27 has a higher corrosion resistance, whereas a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…These proceedings were related in prior works [10,40,51]. The insoluble constituents achieved via the passivation process are complexes of cobalt oxides and cobalt salicylates that impede the metal from dissolving without complicating the electrochemical polymerization technique [51,[53][54][55][56]. By developing polymerization parameters, we were able to achieve composite films of P3MPY-SDS/P2MT that have a significant protective impact.…”
Section: Electrochemical Deposition Of P3mpy-sds/p2mt Coating On Coba...mentioning
confidence: 87%
See 4 more Smart Citations
“…These proceedings were related in prior works [10,40,51]. The insoluble constituents achieved via the passivation process are complexes of cobalt oxides and cobalt salicylates that impede the metal from dissolving without complicating the electrochemical polymerization technique [51,[53][54][55][56]. By developing polymerization parameters, we were able to achieve composite films of P3MPY-SDS/P2MT that have a significant protective impact.…”
Section: Electrochemical Deposition Of P3mpy-sds/p2mt Coating On Coba...mentioning
confidence: 87%
“…Analyzing Figures 5-7 and Tables 1-3, it is indicated that the lowest corrosion speed and the highest protection performance were obtained by the P3MPY-SDS/P2MT composite at 0.9 V and 1.0 V, at current densities of 0.5 mA/cm 2 and 1 mA/cm 2 (at a 5:1 molar ratio, t = 20 min) at current density (at 5:1 and 1:5 molar ratios), and a very good defense was achieved at 1.0 V and 1 mA/cm 2 (at a 1:5 molar ratio, t = 10 min) versus the uncoated substrate in a 1 M HCl environment. The corrosion processes of the composite-coated cobalt alloy and the bare sample in the HCl medium can be effectuated as follows [5,[23][24][25][26][27]35,[52][53][54][55][56][57][58]:…”
Section: Potentiodynamic Polarization Techniquementioning
confidence: 99%
See 3 more Smart Citations